Characterization of the FAD2 Gene Family in Soybean Reveals the Limitations of Gel-Based TILLING in Genes with High Copy Number - Lakhssassi, Naoufal; Zhou, Zhou; Liu, Shiming; Colantonio, Vincent; AbuGhazaleh, Amer; Meksem, Khalid (Frontiers in Plant Science, 2017)
Soybean seed oil typically contains 18-20% oleic acid. Increasing the content of oleic acid is beneficial for health and biodiesel production. Mutations in FAD2-1 genes have been reported to increase seed oleic acid content. A subset of 1,037 mutant families from a mutagenized soybean cultivar (cv.) Forrest population was screened using reverse genetics (TILLING) to identify mutations within FAD2 genes. Although no fad2 mutants were identified using gel-based TILLING, four fad2-1A and one fad2-1B mutants were identified using forward genetic screening and subsequent target sequencing. TILLING has been successfully used as a nontransgenic reverse genetic approach to identify mutations in genes controlling important agronomic traits. However, this technique presents limitations in traits such as oil composition due to gene copy number and similarities within the soybean genome. In soybean, FAD2 are present as two copies, FAD2-1 and FAD2-2. Two FAD2-1 members: FAD2-1A and FAD2-1B; and three FAD2-2 members: FAD2-2A, FAD2-2B, and FAD2-2C have been reported. Syntenic, phylogenetic, and in silico analysis revealed two additional members constituting the FAD2 gene family: GmFAD2-2D and GmFAD2-2E, located on chromosomes 09 and 15, respectively. They are presumed to have diverged from other FAD2-2 members localized on chromosomes 19 (GmFAD2-2A and GmFAD2-2B) and 03 (GmFAD2-2C). This work discusses alternative solutions to the limitations of gel-based TILLING in functional genomics due to high copy number and multiple paralogs of the FAD2 gene family in soybean.